Crimean War 1854 AD (Motives - Events - Repercussions) - جبور علاء (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Research Talks About The War That Broke Out Between Tsarist Russia And The Ottoman Empire In The Year 1854 AD On The Border Areas Between Them, Which Reached Its Climax In The Crimea, And Many European Countries, Including France, Britain And Austria, Intervened In This War, As A Result Of The Multiple Interests Of All These Parties, Including Those The War, Each According To Its Political And Economic Requirements, And All Those European Countries Stood By The Ottomans For Fear Of The Expansion Of The Russian Power And In Order To Preserve The Ottoman Empire In Its Weak Position At The Time, In Line With Ottoman Interests, And That War Went Through Several Stages, Starting With The Russian Occupation Of Some Regions In The Balkans, Including Wallachia And Baghdan, And Ended With The Defeat Of The Russians After The European Armies Joined Forces Against Russia And Destroyed The Russian Military Port On The Black Sea, Sebastpol.